The Effectiveness of Compassion-Focused Acceptance and Commitment Therapy on Pain Acceptance and Catastrophizing of People with Multiple Sclerosis - Farhad Jahangiri; Javad Karimi; Mohsen Razani; Mehdi Roozbahani (Armaghane Danesh Bimonthly Journal, 2023)
Background & aim: Multiple sclerosis (MS) is a progressive chronic disease that can have an effective role on the psychological status of these people due to physical disability and chronic pain. Considering the importance of this issue, the present study was conducted with the aim of investigating the effectiveness of compassion-focused acceptance and commitment therapy on catastrophizing and acceptance of pain in people with MS.